A response time reduction for DC motor controller using SISO technique - Alkhafaji, Falih Salih; Wan Hasan, Wan Zuha; Mohd Isa, Maryam; Sulaiman, Nasri (Institute of Advanced Engineering and Science, 2020)
In an industrial controller, over five decades there are many attempts had been proposed to improve a method of tuning proportional gains of PID controller. Where in the review there is a very little attention have been paid to use satisfactory tuning to get maximum performance. This paper proposes an alternative solution to maximize optimization for a controller-based DC motor. The novel methodology relies on merge proper tuning with optimization using SISO-Optimization technique-based tune ). The comparative study has been done by utilizing classical tuning methods Z N, SIMC, CHR, and AMIGO, to obtain suitable tuning to be joined with . The proposed PID controller was examined in term of response time characteristics. This strategy provides a superior reduction in peak overshoot Pos, dead time td, rise time tr, settling time ts, and peak time tp, that could be utilized to improve the responses of a DC motor controller. Based on comparison results, it was founded that a CHR based SISO_optimization playing a superior role over others in term of Pos 0%, td 0.1811µsec., tr 17.2 µsec, ts30.7 µsec, tp 80 µsec, and the number of iterations iter No 9.Ultimatly,this work overcome the majority of previouse work that related with this approach.